A Identification Of Risk Factors In Dispensing Error In Pharmaceutical Deposit Inpatient Teratai At Fatmawati Hospital Period May-June 2023 - Wulandari, Aprilia (RSUP Fatmawati, 2024)
Medication error is a situation that is detrimental to the patient due to the use of drugs, actions, and treatments since the time of treatment by health workers that are actually able to overcome. One-of-a kind medication errors that often happen are dispensing errors. The purpose of this research is to identify medication errors during the dispensing phase at the Pharmacy Depot of Teratai Inpatient Installation at Fatmawati Hospital. The research method is prospective observation with descriptive analysis. Data processing is done using matrix analysis, grading risks and types of incidents based on the type of hazard to describe incidents and medication error phase dispensing that happened. The research samples of all prescriptions that met the requirements were carried out at the Pharmacy Depot Inpatient Installation at the Teratai Building at Fatmawati Hospital. The research was conducted from May to June 2023. There were 995 recipes with incidental sample errors in as many as 2 recipes in the dispensing phase. The results of the research show that medication errors at the dispensing stage include wrong drug intake (0%), wrong dosage calculation (0%), wrong dosage strength (0%), wrong number of items (0%), wrong label writing (0%), wrong dosage form (0%), and empty drug stock (1.19%). The type of patient safety incident was a KTD, while the results of the risk grading matrix analysis of medication errors related to pharmaceutical services at the inpatient installation of Fatmawati Hospital found that the type of risk grading was low.